City and Town Branding – A Case Study of the Slovenj Gradec Brand (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
The research deals with a relatively young and complex area of branding, i.e. the branding of cities and towns, on the example of Slovenj Gradec brand. The empirical part consists of two approaches to the town's brand recognisability. First, an analysis of in-depth interviews of professional representatives of the six areas or shareholder groups (economy, health care, tourism, culture, education and sport) is presented. Second, an analysis of the survey research is presented with the results in the following areas: the key qualitative elements of the professional public, noticeable characteristics and values (noticeable profile) of the town of Slovenj Gradec, the core of the town's brand (focus), the criteria of urbanism that influence the perception of the town. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.